2015
DOI: 10.1260/1747-9541.10.2-3.285
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Management in Elite Sport: Factors Perceived to Influence Performance

Abstract: Extant sport psychology and sport management research has examined the factors influencing Olympic performance at the athletic and coaching, and governmental and policy levels respectively. In contrast to this abundance of literature, far less is known about the factors perceived to influence performance at the leadership and managerial level. The purpose of this study, therefore, was to investigate the factors that national performance directors (NPDs) operating at this level perceive to influence their role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 94 publications
2
14
0
Order By: Relevance
“…The second higher-order theme in this general dimension was leadership through support staff which involved using staff to reinforce performance expectations and providing appropriate support and motivation to players. Fletcher and Arnold (2011) previously highlighted the leadership of people and staff management as an important element within elite sport (see also, Arnold et al, 2015). The present study's findings support this idea by highlighting how managers utilise committed assistants and coaches to transmit their authority and expectations to players.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The second higher-order theme in this general dimension was leadership through support staff which involved using staff to reinforce performance expectations and providing appropriate support and motivation to players. Fletcher and Arnold (2011) previously highlighted the leadership of people and staff management as an important element within elite sport (see also, Arnold et al, 2015). The present study's findings support this idea by highlighting how managers utilise committed assistants and coaches to transmit their authority and expectations to players.…”
Section: Discussionsupporting
confidence: 77%
“…Beyond the manager's interaction with the players, the findings from the present study revealed that the manager's leadership role off the pitch also required dealing with other key stakeholders, such as the board, support staff, and the media (see also, Arnold et al, 2015). A key finding to emerge was that the manager's leadership role required cooperation with the board, which involved managing relationships upwards and negotiating input into club decisions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While previously blame for the decline has been placed on Federal Government funding of high performance sport (Oakes, 2012), a recent explanation for the decline has been suggested by the AOC's President, John Coates, who claimed it is management and high performance operations that are impacting performance, rather than a lack of funding (Lane, 2012). , Crawford, 2009, Grix and Carmichael, 2012, Houlihan and Zheng, 2013, Arnold et al, 2015. Sam (2009) …”
Section: International Sporting Successmentioning
confidence: 99%
“…Crawford (2009) discovered that there is a fragmented approach to how government manages, supports and communicates with NSOs. Recent literature has examined the role of the National Performance Director (NPD) in the management and leadership of their organisations (Sotiriadou, 2013, Arnold et al, 2015, yet only limited literature examines the management of the relationship between the government and the NSOs (Gowthorp, Toohey & Skinner, 2014 This paper examines this ASC-NSO high performance relationship through an agency theory framework, in order to identify key issues and concerns of the relationship as perceived by ASC and NSO staff. The following section will briefly outline agency theory and its application within the context of non-profit sport organisations.…”
Section: Management and Governance Of High Performance Sport Programsmentioning
confidence: 99%